PENERJEMAHAN INFORMASI IMPLISIT DARI BAHASA INGGRIS KE BAHASA INDONESIA DALAM NOVEL - Anastasia, Faurina (JURNAL TARBAWIYAH, 2015)
A good translation must strive for dynamic equivalence, i.e., the quality of a translation in which the message of the original has been so transported into the receptor language that the response of the receptor is essentially like that of the original receptors. The present study aimed at describing the translation procedures used in translating implicit information in the form of ellipsis and metaphor from English into Indonesian and the equivalence of the translation of those implicit information. Based on the analysis, it was found that the translation procedures which are used to achieve the equivalence are of two types of modulation, namely shift of point of view and explicitation and shift or transposition.